Relationship between Abuse Experience and General Health among Older Adults in Yazd City- Iran - Hassan Rezaeipandari; Mohammad Ali Morowatisharifabad; Vali Bahrevar; Zohreh Rahaei; Ali Hakimzadeh (Elderly Health Journal, 2016)
Introduction: Elder abuse may increase the vulnerability of ageing people to disease and decrease their general health status, so addressing the issue is essential for promoting elderly quality of life. The study aimed to examine the relation between abuse experience and general health among elderly people in Yazd city- Iran.